Yearling scrotal circumference prediction equation and age adjustment factors for various breeds of beef bulls - J.M. Geske; R.R. Schalles; K.O. Zoellner (Kansas Agricultural Experiment Station Research Reports, 1995)
Scrotal circumference measurements and other data were collected on 4,218 Angus, Red Angus, Brangus, Charolais , Gelbvieh, Hereford, Polled Hereford, Limousine, Salers, and Simmental bulls born in the spring of 1991. All were participants in selected on-farm and central bull tests. Our objectives for the study were to develop 205-and 365-day age-adjustment factors for scrotal circumference and derive a 365-day scrotal circumference prediction equation based on adjusted 205-day scrotal circumference. We determined that a 205-day scrotal circumference of approximately 21 cm is necessary to reach 32 cm at 1 year. Age-of-dam adjustment factor for 205-day scrotal circumference is +.8 cm for 2- and 3- year-old dams. The factor for 365-day circumference is +.6 cm for 2-year-old dams.
Keywords: Cattlemen& #x27; s Day; 1995; Kansas Agricultural Experiment Station contribution; no. 95-357-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 727; Beef; Beef cattle; Scrotal circumference; Age adjustment